Effect of variations in music tempo on performance skills of Chinese aerobics athletes - Yang, J.; Jiangang, Q.; Hong, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: While a number of studies have been conducted to explore various training and teaching methods in promoting the development of abilities and skills in sport aerobics (e.g., Hong & Zhang, 2006; Lv & Yu 2000; Tang, 2003), little attention has been directed to investigating whether or not varying the speed of music during performance affects skill levels. By changing the speed of music during practice, the performer learns to take and then adopt physiological and psychological challenges, and in turn will improve his or her movement control and execution. The present study was designed to examine the effect of varying the music tempo during training on skilled performance of Chinese collegiate aerobics athletes. Methods Sixty males and female varsity athletes from a Sports College in the Southwest region of China volunteered to participate in this study. The participants had been involved in training and competition in competitive aerobics for over 5 years and were randomly assigned to either an experimental or control group. The study lasted 16 weeks and consisted of a pre-test and post-test. On the pre-test, each participant was asked to perform a specific aerobics routine and was evaluated based on a scoring rubric which was developed to assess four major components of the performance: movement control, accuracy, fluency, and rhythm. After the pre-test, the participants in the experimental group received the varied speed of music training 3 times per week for 16 weeks whereas the control group participants remained in the traditional training setting during the same period of time. A post-test was conducted after the completion of the 16-week training period with procedures same as the pre-test. The total score was computed on the four components of the aerobics routine for each participant. An independent t test was used to analyze the difference between the mean total score of the experimental group and the control group. Results The results of the study revealed a significant difference (p<.05) in aerobics performance between the two groups with the experimental group demonstrating a higher mean score than the control group.